Influencia de la desigualdad de género en la calidad de vida de las familias del caserío Calera Baja – Chepén 2019 - Vera Santos, Víctor Raúl (2022)
Through this research work entitled: influence of gender inequality on the quality of life of families of the caserio Calera Baja - Chepen 2019. It was possible to determine the influence of gender inequality expressed in inadequate sociocultural patterns and the macho social environment, in the quality of life of the families of the Calera Baja village. In the construction of this report, methods such as ethnographic, deductive, inductive and statistical were used, in addition to the techniques together with their instruments such as the interview and its interview guide, observation and its guide, and finally the survey wit its questionnaire. The results of this study allow us to understand the influence that gender inequality exerts on the quality of life of the families of the Calera Baja farmhouse, due to the fact that violent attitudes ,inadequate sexist education, a macho socio-family environment and the inadequate distribution of roles, they perpetuate gender equality gaps and transmit them from generation to generation.